2002
DOI: 10.1136/gut.51.4.567
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking, appendectomy, and tonsillectomy as risk factors for the development of primary sclerosing cholangitis: a case control study

Abstract: Background and aims: The strong clinical association between primary sclerosing cholangitis (PSC) and ulcerative colitis (UC) suggests common factors in their pathogenesis. Smoking, previous appendectomy, and tonsillectomy have been associated with a decreased risk of developing UC. In this study, our aim was to examine these risk factors in patients with PSC with and without underlying inflammatory bowel disease (IBD). Methods: The smoking habits and history of previous appendectomy and/or tonsillectomy of 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
1
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 43 publications
6
54
1
2
Order By: Relevance
“…Moreover, this protective effect was more marked in patients with primary sclerosing cholangitis than ulcerative colitis and was seen in patients with and without inflammatory bowel disease [29][30][31] . The mechanism of protection in both disorders remains unknown.…”
Section: Risk Factorsmentioning
confidence: 95%
“…Moreover, this protective effect was more marked in patients with primary sclerosing cholangitis than ulcerative colitis and was seen in patients with and without inflammatory bowel disease [29][30][31] . The mechanism of protection in both disorders remains unknown.…”
Section: Risk Factorsmentioning
confidence: 95%
“…One study found that current cigarette smoking in UC patients increased the risk of articular and dermatological EIMs, whereas no such increase was observed in ocular or hepatobiliary complications. 38 Current or previous smoking has also been shown to reduce instances of primary sclerosing cholangitis 1,5,6,24,[39][40][41] and backwash ileitis. 24 The literature remains divided, however, regarding smoking's effect on pouchitis following colectomy with ileal pouch-anal anastomosis.…”
Section: 21mentioning
confidence: 99%
“…Environmental factors are also involved with the absence of cigarette smoking appearing to be a predisposing risk factor [7,8], which is independent of the presence of IBD. In one study, only 4.9% of patients with PSC smoked compared with 26.1% of controls [9].…”
Section: Epidemiologymentioning
confidence: 99%